Performance improvement of set of worm gears used in soot blower through profile modification - Honkalas, Rahul; Deshmukh, Bhagyesh; Pawar, Prabhakar; Salunkhe, Sachin; Cep, Robert; Abouel Nasr, Emad (Frontiers in Mechanical Engineering, 2024)
The present design of the Set of Worm Gear utilized for a Soot Blower, manufactured by one manufacturer, has an efficiency of 68.8%. The Soot Blower is one of the most critical industrial application to remove the vast amount of generated soot from the boiler. It is required by 24 x 7 operational hours. Energy consumption depends on the soot blower's working efficiency and, ultimately, the design of the Set of Worm Gear. This paper mainly focuses on the design investigation and analysis of the available industrial Set of Worm Gear used in a Soot Blower. The theoretical, experimental, and FEA approaches are validated to check the Set of Worm Gear stability under input conditions. This paper also describes the procedure for the analytical design of experimentation (DOE) approach to identify the most significant factor in performance (efficiency) improvement. Further suggested required design improvements for the Set of Worm Gear using profile modification approach. This is basically for improvement in the efficiency of the current industrial design Set of Worm Gear used in a Soot Blower. Analytical design of experimentation (DOE) approach successfully identifies Worm Wheel Teeth in number (letter, Z2) and Gear Module (letter, m) are the two most significant factors in which performance (efficiency) varies. Final performance (efficiency) is improved from 68.8% to 74.6%, an 8.5% incremental. This results in lower power consumption in industrial applications.